2011
DOI: 10.1159/000331772
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Rosiglitazone Administration to Neonatal Rat Pups Does Not Alter the Young Adult Metabolic Phenotype

Abstract: Background: Rosiglitazone (RGZ), a peroxisome proliferator-activated receptor-γ (PPARγ) agonist, significantly enhances lung maturation without affecting blood biochemical and metabolic profiles in the newborn period. However, whether this exposure to RGZ in neonatal life alters the adult metabolic phenotype is not known. Objective: To determine the effects of early postnatal administration of RGZ on the young adult metabolic phenotype. Methods: Newborn rat pups were administered either saline or RGZ for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…cardiovascular effects with RGZ, and bladder cancer with PGZ ( 14 17 , 26 ). In line with our prior studies, where we have shown that RGZ given parenterally, either antenatally or postnatally, doesn’t affect either cardiac troponin or any of the other metabolic parameters examined, such as the blood lipid profile and glucose and insulin tolerance tests ( 3 , 11 13 ), in this study too, plasma cardiac troponin levels were undetectable in both control and hyperoxia-exposed animals with or without PGZ treatment.…”
Section: Discussionsupporting
confidence: 92%
“…cardiovascular effects with RGZ, and bladder cancer with PGZ ( 14 17 , 26 ). In line with our prior studies, where we have shown that RGZ given parenterally, either antenatally or postnatally, doesn’t affect either cardiac troponin or any of the other metabolic parameters examined, such as the blood lipid profile and glucose and insulin tolerance tests ( 3 , 11 13 ), in this study too, plasma cardiac troponin levels were undetectable in both control and hyperoxia-exposed animals with or without PGZ treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Since hypoxia and hyperoxia have similar consequences for the TGF-β/WNT/β-catenin/PPARγ pathways, this requires a fine tuning of oxygen use in very premature infants. Numerous studies have shown PPARγ agonists have a beneficial effect on lung maturation and may provide a potentially safe lung therapy (53, 54, 115, 146, 147, 157, 196, 197). Nebulized PPARγ agonists may represent a potential strategy for improving postnatal lung maturation, both by inhibition of the TGF-β/WNT/β-catenin pathway and by preventing neonatal hyperoxia-induced lung injury in premature BPD infants, thereby reducing morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…In an animal model, the systemic administration of RGZ, either antenatally or postnatally, enhances lung maturation and can prevent hyperoxia-induced acute neonatal lung injury. This strongly suggests that PPARγ agonists could potentially play an important role in preventing and/or treating BPD (53, 115, 146, 147).…”
Section: Pparγ Agonists and Bpdmentioning
confidence: 99%
“…Recent studies have also shown that PPAR γ agonists such as rosiglitazone (RGZ) significantly enhance lung maturation when administered antenatally. Its efficacy in enhancing pulmonary maturation and neonatal and long-term safety following postnatal administration has also been demonstrated recently [ 5 , 6 ]. In those studies, lack of any significant impact on the neonatal and long-term metabolic profile of the exposed offspring was demonstrated [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its efficacy in enhancing pulmonary maturation and neonatal and long-term safety following postnatal administration has also been demonstrated recently [ 5 , 6 ]. In those studies, lack of any significant impact on the neonatal and long-term metabolic profile of the exposed offspring was demonstrated [ 5 , 6 ]. However, data on the long-term effects of RGZ are sparse, and to date no study has examined the effects of RGZ on the metabolic profile of adult rats when administered prenatally.…”
Section: Introductionmentioning
confidence: 99%